1996
DOI: 10.1042/bj3200847
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for regulated dimerization of cell-cell adhesion molecule (C-CAM) in epithelial cells

Abstract: C-CAM is a Ca(2+)-independent cell adhesion molecule (CAM) belonging to the immunoglobulin superfamily. Addition of chemical cross-linkers to isolated rat liver plasma membranes, intact epithelial cells and purified preparations of C-CAM stabilized one major C-CAM-containing product whose apparent molecular mass was approximately twice that of the C-CAM monomer. The failure to detect additional proteins after cleavage of the cross-linked species demonstrated that C-CAM exists as non-covalently linked dimers bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 53 publications
3
66
0
1
Order By: Relevance
“…One possibility is that C-CAM2 regulates the activity of the cytoplasmic domain of C-CAM1. The recent finding that C-CAM can form dimers (Hunter et al 1996) supports such an idea.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…One possibility is that C-CAM2 regulates the activity of the cytoplasmic domain of C-CAM1. The recent finding that C-CAM can form dimers (Hunter et al 1996) supports such an idea.…”
Section: Discussionsupporting
confidence: 58%
“…It has been suggested that they function as adhesion molecules that organize the sodium channel in specific locations in neurons (Isom and Catterall 1996). Supramolecular complexes of C-CAM have been described in several cell types (Hunter et al 1996). Finally, it has recently been found that C-CAM1 is a negative regulator of cellular growth and that it can suppress tumorigenesis of prostate and colon carcinoma cells (Hsieh et al 1995;Kunath et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to observe the seemingly dimeric form of hepaCAM and its mutant in their respective un-cross-linked samples. Although the mechanism resulting in such interaction is unknown to us, Hunter et al (5) and others (12) have observed a similar phenomenon in C-CAM and raise the possibility that C-CAM dimers become covalently linked, perhaps through the action of transglutaminase, an enzyme which catalyzes the formation of ␥-glutamyl-⑀-lysine bonds in a restricted number of cellular proteins. Subcellular localization of hepaCAM in nonpolarized MCF7 cells showed that hepaCAM molecules were recruited to the cytoplasmic membranes at sites of cell-cell attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dimerization of selectins has been shown to enhance adhesive tethers (60). Interestingly, dimerization of CEACAM-1 and CEACAM-2 is regulated by calmodulin and calcium ions (68), highlighting the importance of inside-out signaling mechanisms. ICAM-1 exists predominantly as a dimer at the cell surface and binds in this dimeric state with greatly enhanced affinity to the integrin LFA-1 compared with its monomeric form (43).…”
Section: Discussionmentioning
confidence: 99%